Influences on growth and survival of seedlings planted in black ash stands of Northern Michigan and Wisconsin - Seth W. Davenport; Dustin R. Bronson; Kathryn Hofmeister; Randall K. Kolka; Grady Boyle; Fengjing Liu (Forest Ecology and Management, 2026)

Integrating nitrogen and carbon cycling into LANDIS-II/PnET-Succession to improve forest landscape modeling: methods and sensitivity analyses - Zaixing Zhou; Eric J. Gustafson; Scott V. Ollinger; Andrew P. Ouimette; Brian R. Miranda; Matthew J. Duveneck; Jane R. Foster; Brian R. Sturtevant; Dustin R. Bronson; Danelle Laflower (Ecological Modelling, 2025)

Desired REgeneration through Assisted Migration (DREAM): Implementing a research framework for climate-adaptive silviculture - Alejandro A. Royo; Patricia Raymond; Christel C. Kern; Bryce T. Adams; Dustin Bronson; Emilie Champagne; Daniel Dumais; Eric Gustafson; Paula E. Marquardt; Amanda M. McGraw; Jessica R. Miesel; Alison D. Munson; et al. (Forest Ecology and Management, 2023)

Linked disturbance in the temperate forest: Earthworms, deer, and canopy gaps - Samuel P. Reed; Dustin R. Bronson; Jodi A. Forrester; Leah M. Prudent; Anna M. Yang; Austin M. Yantes; Peter B. Reich; Lee E. Frelich (Ecology, 2023)
Despite the large body of theory concerning multiple disturbances, relatively few attempts have been made to test the theoretical assumptions of how and if disturbances interact. Of particular importance is whether disturbance events are linked, as this can influence the probability and intensity of ecological change. Disturbances are linked when one disturbance event increases or decreases the likelihood or extent of another. To this end, we used two long‐term, multi‐disturbance experiments in northern Wisconsin to determine whether earthworm invasion is linked to canopy gap creation and white‐tailed deer browsing. These three disturbances are common and influential within North American temperate forests, making any interactions among them particularly important to understand. We expected both deer and canopy gaps to favor invasive earthworms, particularly species that live close to or on the soil surface. However, we found only partial support of our hypotheses, as both deer exclosures and canopy gaps decreased earthworms in each experiment. Further, earthworm density increased the most over time in areas far from the gap center and in areas with deer present. Deer exclosures primarily decreased Aporrectodea and Lumbricus species, while gaps decreased Dendrobaena and Lumbricus species. Our findings show that earthworm invasion is linked to deer presence and gap‐creating disturbances, which provides new insight in multiple disturbance theory, aboveground–belowground dynamics, and temperate forest management.

The case for stand management guidelines as dynamic as global change: Aspen forest stockings of the western Great Lakes - Michael T. Carson; John M. Zobel; Dustin R. Bronson; Amanda M. McGraw; Christopher W. Woodall; Christel C. Kern (Forest Ecology and Management, 2023)

Evaluating effectiveness of girdle-herbicide containment of below-ground spread of oak wilt (Bretziella fagacearum) - Dustin R. Bronson; Jed Meunier; Teresa R. Pearson; Kyoko Scanlon (Forest Ecology and Management, 2023)

Seasonal photosynthetic gas exchange and water-use efficiency in a constitutive CAM plant, the giant saguaro cactus (Carnegiea gigantea) - Dustin R. Bronson; Nathan B. English; David L. Dettman; David G. Williams (Oecologia, 2011)

Effect of ecosystem warming on boreal black spruce bud burst and shoot growth - DUSTIN R. BRONSON; STITH T. GOWER; MYRON TANNER; INGRID VAN HERK (Global Change Biology, 2009)
The boreal forest is predicted to experience the greatest warming of any forest biome during the next 50–100 years, but the effects of warming on vegetation phenology are not well known. The objectives of this study were to (1) examine the effects of whole ecosystem warming on bud burst and annual shoot growth of black spruce trees in northern Manitoba, Canada and (2) correlate bud burst to cumulative degree‐days (CDD). The experimental design was a complete randomized block design that consisted of four replicated blocks. Each replicate block contained four treatments: soil warming only (heated outside, HO), soil and air warming (heated inside, HI), control outside (no chamber, no heating, CO), and inside a chamber maintained at ambient conditions (no soil or air warming, control inside, CI). Bud burst was measured during the first and second years of the experiment, starting in 2004, and annual shoot growth was measured for the first 3 years (2004–2006) of the study. On average, shoot bud burst occurred 11 and 9 days earlier in 2004 and 2005, respectively, for HI than for other treatments. However, mean CDD required for bud burst for HI was within the standard deviation of CO for both years. In year 1 of the treatments, shoot bud burst occurred earlier for HI than other treatments (CI, CO, HO), but final shoot length of HI trees was less than in CO trees. In the second year of warming, final shoot length was not different for HI than CO. By the third year of warming final shoot length was significantly greater for HI than all other treatments. Empirical results from this study suggest that soil and air warming causes an earlier bud burst for all years of observation and greater shoot lengths by the third season of warming. A longer growing season and greater annual shoot growth should increase carbon uptake by boreal black spruce trees in a warmer climate.

Response of soil surface CO 2 flux in a boreal forest to ecosystem warming - DUSTIN R. BRONSON; STITH T. GOWER; MYRON TANNER; SUNE LINDER; INGRID VAN HERK (Global Change Biology, 2008)
Soil surface carbon dioxide (CO 2 ) flux ( R S ) was measured for 2 years at the Boreal Soil and Air Warming Experiment site near Thompson, MB, Canada. The experimental design was a complete random block design that consisted of four replicate blocks, with each block containing a 15 m × 15 m control and heated plot. Black spruce [ Picea mariana (Mill.) BSP] was the overstory species and Epilobium angustifolium was the dominant understory. Soil temperature was maintained (∼5 °C) above the control soil temperature using electric cables inside water filled polyethylene tubing for each heated plot. Air inside a 7.3‐m‐diameter chamber, centered in the soil warming plot, contained approximately nine black spruce trees was heated ∼5 °C above control ambient air temperature allowing for the testing of soil‐only warming and soil+air warming. Soil surface CO 2 flux ( R S ) was positively correlated ( P 2 flux ( R S ) was 24% greater in the soil‐only warming than the control in 2004, but was only 11% greater in 2005, while R S in the soil+air warming treatments was 31% less than the control in 2004 and 23% less in 2005. Live fine root mass ( P